1998
DOI: 10.1037/0735-7036.112.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation of play elicits high-frequency ultrasonic vocalizations in young rats.

Abstract: The authors provide initial documentation that juvenile rats emit short, high-frequency ultrasonic vocalizations (high USVs, approximately 55 kHz) during rough-and-tumble play. In an observational study, they further observe that these vocalizations both correlate with and predict appetitive components of the play behavioral repertoire. Additional experiments characterized eliciting conditions for high USVs. Without prior play exposure, rats separated by a screen vocalized less than playing rats, but after onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
322
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 410 publications
(338 citation statements)
references
References 33 publications
12
322
3
1
Order By: Relevance
“…We have observed this in two separate situations. First, in sequential daily play sessions, the amount of chirping that occurs during a session is correlated with the number of dorsal contacts (play solicitations) emitted during play testing [38]. Second, when we bred animals for high chirping, we also found that these animals exhibited significantly more play solicitations than randomly selected and low-chirp lines [63].…”
Section: Positive Relations Between Playing and Ticklingmentioning
confidence: 81%
See 3 more Smart Citations
“…We have observed this in two separate situations. First, in sequential daily play sessions, the amount of chirping that occurs during a session is correlated with the number of dorsal contacts (play solicitations) emitted during play testing [38]. Second, when we bred animals for high chirping, we also found that these animals exhibited significantly more play solicitations than randomly selected and low-chirp lines [63].…”
Section: Positive Relations Between Playing and Ticklingmentioning
confidence: 81%
“…50-kHz chirping is evoked most robustly by the positive social interchange of rough-and-tumble play, and even more so by human tickling Sustained bouts of human laughter are evident in children during tickling and rough-and-tumble play, especially when they are chasing each other [80,90]. A similar type of vocal activity (chirping at about a frequency of 50 kHz, which humans cannot hear without special equipment, of course) is also evident when young rats play [38]. To our knowledge, play and tickling are by far the most robust initiators of the short 50-kHz chirps that are also common at much lower levels in other positive social situation [13].…”
Section: The Weight Of Evidence For Rat ''Laughter''mentioning
confidence: 96%
See 2 more Smart Citations
“…In fact, it has been found that sound rates, type of calls, and acoustic structure within a call may vary depending on the context of behaviors such as aggression, panic, and social separation (rodents: Goldstein et al, 1996;Albeck et al, 1997;primates: Bayart et al, 1990;Champoux and Suomi, 1994;Friedman et al, 1995;Laudenslager et al, 1995;Boinski et al, 1999;farm animals: von Borell and Ladewig, 1992;Désautés et al, 1997;Weary et al, 1997). Animals living in a controlled environment with predictable daily routines, experience anticipation which is a mental state that can infl uence their behaviors including vocalizations (Krishnamurthy, 1994;Knutson et al, 1998;Burgdorf et al, 2000;Waitt and Buchanan-Smith, 2001;Ulyan et al, 2006;Düpjan et al, 2008;Gilbert-Norton et al, 2009;Polizzi di Sorrentino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%